2006
DOI: 10.1002/pat.681
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability and degradation kinetics of poly(methyl methacrylate)/layered copper hydroxy methacrylate composites

Abstract: Abstract:Poly(methyl methacrylate) (PMMA)/copper hydroxy methacrylate (CHM) composites were prepared via solution blending and bulk polymerization. Addition of 3% by weight of the CHM additive using solution blending resulted in a significant increment (∼45°C) in thermogravimetric NOT THE PUBLISHED VERSION; this is the author's final, peer-reviewed manuscript. The published version may be accessed by following the link in the citation at the bottom of the page. Technology, Vol. 17, No. 4 (April 2006): pg. 312-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
52
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 53 publications
6
52
0
2
Order By: Relevance
“…Isoconversional methods do not suffer from that drawback and enables the determination of the dependency of Ea on the extent of reaction and are therefore favored over model-fitting methods [37], [38] and [39]. Both isothermal and non-isothermal methods have been used in the determination of kinetic parameters in the degradation of polymers [17], [29], [40], [41] and [42].…”
Section: Kinetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Isoconversional methods do not suffer from that drawback and enables the determination of the dependency of Ea on the extent of reaction and are therefore favored over model-fitting methods [37], [38] and [39]. Both isothermal and non-isothermal methods have been used in the determination of kinetic parameters in the degradation of polymers [17], [29], [40], [41] and [42].…”
Section: Kinetic Analysismentioning
confidence: 99%
“…Recently another class of layered materials, anionic clays, have also generated interest as potential fire retardants and the most widely investigated materials in this class are the layered double hydroxide (LDH) [11] and [12]. LDHs are materials which are related to the mineral hydrotalcite and have a general formula which is represented as [M 2+ 1−xM 3+ x(OH)2]A n− x/n.yH2O, where M 2+ is a divalent Other closely related classes of anionic clays, hydroxy double salts (HDS) and layered hydroxy salts (LHS), although not extensively studied as LDH, have similarly been shown to have potential as fire retardants [17], [18] and [19]. In HDSs and LHSs, the metal hydroxide layers are composed of divalent cations represented as M 2+ and Me 2+ and are formulated as [M 2+ 1−x Me 2+ 1+x (OH)3(1−y)] x+ (A n− (1+3y)n)·m H2O.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work in our laboratory has shown that the addition of copper-containing HDSs or LHSs to poly(methyl methacrylate) 10,11 or poly(vinyl ester) 12,13 results in enhanced thermal stability. Significant reductions were observed in total heat release, as measured via cone calorimetry, and there was an increase in the amount of char formed compared with the virgin polymer.…”
mentioning
confidence: 99%
“…The presence of reduced metallic species has been shown to play an important role in thermal stabilization of polymeric composites. [10][11][12][13]47,48 Klenov and co-workers 49 reported the appearance of Cu(I) and metallic copper on the surface of the Cu 2+ -containing ZnO after catalyst reduction and they believe these species play an important role in the catalytic synthesis of methanol from H2 and CO. The formation of reduced copper is thus important for enhancing selected chemical pathways.…”
mentioning
confidence: 99%
“…The weight loss with third stage (about 360 o C) associated with random scission of the polymer backbone. 12 The TGA thermogram of the Ash (5 wt %)/ PMMA composite also presented three stage decomposition. The thermogram clearly indicated that the second and third stage of decomposition of the composite were shift to higher temperature as compared to pure PMMA.…”
Section: Resultsmentioning
confidence: 99%